This story might save your life : a novel - Crum, Tiffany (Pine & Cedar, 2026)
"Benny Abbott and Joy Moore host one of the most beloved podcasts in the world. Each week, they delight listeners with a different "against-all-odds" survival story, gleefully finding the weird, life-affirming humor in near-death experiences. Since their first episode on Joy's experience with severe narcolepsy, they've been the best friends everyone wants to befriend - and thanks to the meticulous management of Joy's husband Xander, they've built a lucrative empire. The problem is, their next survival story may be their own. When Benny arrives at Joy and Xander's one morning to record, he finds shattered glass and an empty house. The one clue shedding light on the couple's disappearance is the incomplete, previously-unseen first draft of Joy's memoir. Benny is desperate to find them, even when the police soon zero in on him as their prime suspect. Millions of devoted listeners think they know the "real" Benny and Joy. But as the hours tick by, and the odds seem increasingly stacked against Joy and Xander being found alive, not even the most devoted fans could guess the secrets their favorite famous BFFs have hidden from the world - and from each other"-- Provided by publisher.